(untitled) (Minerva, 2019)
Three great traditions (Jewish, classic and Christian) come together in the novel of Frankenstein. All of them have a common point: transgression. This is a characteristic theme of Greek tragedy, and it became very prolific in Romanticism. Transgression fits very well with the distinctive spirit of freedom that was prevalent during that period and the exploration of the irrational world, which is always all-pervading in gothic accounts. Similar to Greek tragedy, transgression in the novel of Frankenstein is developed from a man’s act of arrogance towards the gods, which unites the concepts of wickedness, transgression and tragedy. In this article I will analyze the relationship between Mary Shelley and Greek tragedy, which is reinterpreted from a Romantic point of view. To do so, I will refer to Classic tradition in Shelley’s novel and, more specifically, to the connections with the three prominent Greek dramatists: Aeschylus, Sophocles, and Euripides.